Developing Website-Based Gamification Learning Media on Debate Texts in Indonesian Language Learning - Diana, Purwati Zisca; Indriyani, Ika Putri; Sulistiyono, Roni; Wulandari, Putri Ayu; Prafitra, Revola Aridya (Journal of Languages and Language Teaching, 2024)
This research and development is motivated by the lack of creative learning media in Indonesian language learning, especially in grade X high school debate text material. Therefore, there is a need to develop website-based gamification learning media that makes learning more creative and innovative. Until the researcher developed the Website-Based "Adventure of Gama" Gamification in Class to determine the feasibility of developing website-based "Adventure of Gama" gamification in class X high school debate texts, and (3) to determine the effectiveness of the gamification trials being developed. This research uses the Research and Development (R&D) research method, using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development procedure. In this research, the ADDIE development procedure. The subjects in this research were class X high school students The data collection technique and instrument used in this research is a questionnaire sheet, while the information analysis technique used is quantitative descriptive data analysis. The research results show that the learning media developed is in the "Very Good" category. This is proven by obtaining an average score of 85.2 and is suitable for testing to obtain an effectiveness test. The average obtained from material experts was 100, from media experts as much as 78.8, and teaching experts as much as 77. Based on these results, it can be concluded that research into the development of website-based "Adventure of Gama" Gamification in Class X High School Debate Texts was used as media. learning that can motivate students to follow the Indonesian language learning series, especially in debate material.